MULTIMEDIA INTERACTIVE TOOLS IN PROGRAMMING TEACHING - L. M. Medzhitova; R. T. Fazilova; E. I. Ablyalimova (Kherson State University, 2011)
Use of multimedia interactive tools while teaching programming for freshmen, is considered. The use of multiple-mouse applications are proposed for raising student's activities